Aplikasi Pembelajaran Organ Tubuh Manusia dengan Teknologi Augmented Reality Berbasis Markerless Untuk Sekolah Dasar - Findyka Ayuningtyas; Yuli Asriningtias (Bulletin of Computer Science Research, 2025)
The rapid development of technology in the modern era has led to the education sector being required to innovate learning activities that are more interesting, effective, and efficient. In the education sector, the challenge in biology learning materials is the lack of interest in learning caused by learning media that still use printed or physical books. Physical learning media such as images and text are less effective in explaining conceptual material, especially in human anatomy material that requires students to learn with geometric visualization skills. A potential solution to this issue involves applying Augmented Reality (AR) technology through a markerless approach. The development method used is the waterfall software development method. AR is a technology that integrates digital components with the physical environment, allowing users to interact with virtual objects via mobile devices, especially those utilizing the Android operating system.  The markerless method allows students to use an AR camera and display human organ objects without using markers. This research aims to introduce human body organs with Augmented Reality technology in the form of three-dimensional objects with a markerless method to reduce complexity, provide an interactive learning experience with rotation and scaling features of three-dimensional objects to improve students' visualization understanding of anatomy, as well as quiz features to hone students understanding.